Effects of Probiotic Supplementation on Inflammatory Markers and Glucose Homeostasis in Adults With Type 2 Diabetes Mellitus: A Systematic Review and Meta-Analysis - Ding, Li-Na; Ding, Wen-Yu; Ning, Jie; Wang, Yao; Yan, Yan; Wang, Zhi-Bin (Frontiers in Pharmacology, 2021)
Background: Several studies have revealed the effect of probiotic supplementation in patients with type 2 diabetes (T2DM) on the amelioration of low-grade inflammation, which plays an important role in the pathogenesis of T2DM. However, the effects of the clinical application of probiotics on inflammation in individuals with T2DM remain inconsistent. This study aims to investigate the comprehensive effects of probiotics on inflammatory markers in adults with T2DM. Methods: PubMed, Embase, Cochrane Library, and the Web of Science were searched to identify randomized controlled trials (RCTs) exploring the effect of probiotic supplementation on inflammatory markers in individuals with T2DM through March 11, 2021. Two reviewers independently screened the literature, extracted data, and assessed the risk of bias of the included studies. We used a random-effects model to calculate the standardized mean difference (SMD) between the probiotic supplementation and control groups. Results: Seventeen eligible studies were selected with a total of 836 participants, including 423 participants in probiotic supplementation groups and 413 participants in control groups. Our study demonstrated that compared with the control condition, probiotic intake produced a beneficial effect in reducing the levels of plasma inflammation markers, including tumour necrosis factor-α (TNF-α) (SMD [95% CI]; -0.37 [-0.56, -0.19], P＜0.0001) and C-reactive protein (CRP) (SMD [95% CI]; -0.21 [-0.42, -0.01], P=0.040), while it had no effect on the plasma interleukin-6 (IL-6) level (SMD [95% CI]; -0.07 [-0.27, 0.13], P=0.520). In addition, our results support the notion that probiotic supplementation improves glycaemic control, as evidenced by a significant reduction in fasting blood glucose (FPG), HbA1c and HOMA-IR (SMD [95% CI]: -0.24 [-0.42, -0.05], P=0.010; -0.19 [-0.37, -0.00], P=0.040; -0.36 [-0.62, -0.10], P=0.006, respectively). Conclusion: Our study revealed some beneficial effects of probiotic supplementation on improving inflammatory markers and glucose homeostasis in individuals with T2DM. Probiotics might be a potential adjuvant therapeutic approach for T2DM.